Jairus, His Daughter and the Haemorrhaging Woman (Mk 5.21-43; Mt. 9.18-26; Lk. 8.40-56) Research Survey of a Gospel Story about People in Distress - Zwiep, Arie W. 1964- (2015)
This article examines the history of interpretation of the pericope of the healing of the haemorrhaging woman and the raising of Jairus’ daughter (Mk 5.21-43; Mt. 9.18-26; Lk. 8.40-56). It starts with the earliest attempts to harmonize the synoptic accounts, and reviews medieval allegorical interpretations, historical-critical theories, including the apparent death (coma) theory, D.F. Strauss and mythical interpretation, form-criticism, the question of sources, literary and narrative approaches, socio-critical (feminist) interpretation, psychoanalytical criticism, and contextual (poststructural) readings.
Keywords: Bibel; Bibel; Bibel; Structuralism; source- and redaction criticism; Poststructuralism; psychoanalytical interpretation; Narrative Criticism; mythical interpretation; miracle story; Jairus’ daughter; Historical Criticism; Haemorrhaging Woman; Feminist Criticism; Allegorical Interpretation